If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + (4b + 2) * I = 9 + -6I Reorder the terms: 3a + (2 + 4b) * I = 9 + -6I Reorder the terms for easier multiplication: 3a + I(2 + 4b) = 9 + -6I 3a + (2 * I + 4b * I) = 9 + -6I 3a + (2I + 4bI) = 9 + -6I Reorder the terms: 2I + 3a + 4bI = 9 + -6I Solving 2I + 3a + 4bI = 9 + -6I Solving for variable 'I'. Move all terms containing I to the left, all other terms to the right. Add '6I' to each side of the equation. 2I + 3a + 6I + 4bI = 9 + -6I + 6I Reorder the terms: 2I + 6I + 3a + 4bI = 9 + -6I + 6I Combine like terms: 2I + 6I = 8I 8I + 3a + 4bI = 9 + -6I + 6I Combine like terms: -6I + 6I = 0 8I + 3a + 4bI = 9 + 0 8I + 3a + 4bI = 9 Add '-3a' to each side of the equation. 8I + 3a + -3a + 4bI = 9 + -3a Combine like terms: 3a + -3a = 0 8I + 0 + 4bI = 9 + -3a 8I + 4bI = 9 + -3a Reorder the terms: -9 + 8I + 3a + 4bI = 9 + -3a + -9 + 3a Reorder the terms: -9 + 8I + 3a + 4bI = 9 + -9 + -3a + 3a Combine like terms: 9 + -9 = 0 -9 + 8I + 3a + 4bI = 0 + -3a + 3a -9 + 8I + 3a + 4bI = -3a + 3a Combine like terms: -3a + 3a = 0 -9 + 8I + 3a + 4bI = 0 The solution to this equation could not be determined.
| 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 | | -n+n= | | 2(4z-2)-2(5-3z)=4 | | 5x+5=4x+4 | | 11+2(3n-11)=1 | | 6((2n^2)+3n-35)=0 | | (3x+4)-30=0 | | t-45=-48 | | 4x+8y-3x+2y= | | 1x+2y=18 | | 12+3(z-4)=-5z+5 | | -3(x+12)=16-x | | -6(n+3)+21=-3n-6 | | -2(2x+5)= | | 1x+2y+3z=18 | | (2x+13)=-81 | | 4(2x-6)= | | 17-13=2(x-6) | | 2u^2+2v^2+4=0 | | (2x-6)=28 | | 5(3c-1)-2=12c+2 | | -6x+12=2(3x-4) | | -2v-16=-8v+40 | | 4t-4=5(t+4) | | Y=-0.3X^2+4X-1 | | (x+17)=24 | | C=0.45m+3.60 | | x+5+x+9=90 | | 1.6q-4.3+2.1q=10.5 |